Applicability of Positive Cooperativity Model in Surfactant Mediated Chemical Reaction - London Singh, R.K.; Srivastava, S.K.; Niraj Luwang, M. (Asian Journal of Chemistry, 2010)
Reaction of crystal violet carbonium ion with hydroxide has been investigated in micellar media under pseudo-first order condition. The reaction is strongly catalyzed in the presence of cetyl trimethyl ammonium bromide (CTAB) micelle, but is inhibited in presence of sodium dodecyl sulphate (SDS) micelle. This can be explained by considering both the electrostatic and hydrophobic interactions which are simultaneously operating in the reaction system. Quantitative analysis of the micellar data obtained is done by applying positive cooperativity model of enzyme catalysis. Presences of counter ions on the reaction system further inhibit the reaction rates. Thermodynamic activation parameters and binding constants have also been evaluated.